Promoting High-Quality Development of Shaanxi’s Manufacturing Industry with Digital-Physical Integration as a New Feature - Zhao, Jiahui; Wang, Tieshan; Yang, Tong (Asia Pacific Economic and Management Review, 2025)
The Third Plenary Session of the 20th CPC Central Committee has arranged for "improving the system for deep integration of the real economy and the digital economy," requiring continuous deepening of the integration of informatization and industrialization and vigorously advancing the high-quality development of the manufacturing industry. On the path of the new era and new guidelines, the key to implementing this arrangement lies in accelerating the popularization and application of a new generation of information technology across all fields and industrial chains, and fully unlocking the value of data elements. Promoting the deep integration of the real economy and the digital economy is a strategic choice to seize the opportunities of the new round of scientific and technological revolution and industrial transformation. It is also an indispensable path for building a modern industrial system and realizing the high-quality development of the manufacturing industry in the new development stage.